Doğru Bilgi, Sanal Gerçeklik, İyi Kütüphanecilik - M. Tayfun Gülle (Türk Kütüphaneciliği)
Departing from the idea that internet, which has become a deep information tunnel, is causing a problem in access to “accurate information”, it is expressed that societies are imprisoned within the world of “virtual reality” with web 2.0/web 3.0 technologies and social media applications. In order to diagnose this problem correctly, the media used from past to present for accessing information are explained shortly as “social tools.” Furthermore, it is emphasised and summarised with an editorial viewpoint that the means of reaching accurate information can be increased via the freedom of expression channel which will be brought forth by “good librarianship” applications. IFLA Principles of Freedom of Expression and Good Librarianship is referred to at the end of the editorial.